The Strengthening Role of Proportion Women on Supervisory Board on The Correlation Among Firm Size and ESG Disclosure - Muhammad Putra Aprullah; Rulfah M Daud (Jurnal Manajemen, Akuntansi, Ekonomi, 2026)
This study examines the role of proportion of women on the supervisory board in the correlation among firm size and ESG disclosure. Unbalanced panel data is used to comprise 1518 non-financial companies listed on the Indonesia Stock Exchange (IDX) period 2018–2023. Moderated regression analysis (MRA) analyse hypothesis testing to estimate the direct effects of company size and the proportion of women, as well as their interaction effects on the level of ESG disclosure. The results of study show that Firm size has positively effect on ESG disclosure, and the proportion women on the supervisory board positively effects on ESG disclosure. The proportion women on the supervisory board strengthens the effect of firm size on ESG disclosure. This study enriches and highlights the added value of proportion women in the oversight function and the quality of sustainability decisions. Theoretically, this study enhances legitimacy, upper echelon, and gender socialization theory in corporate governance and sustainability practice. Practically, this study contributes as knowledge for investors, regulators, and companies to consider the relevance of women on supervisory boards and firm size as a governance indicator for promoting ESG disclosure.